The observed postglacial recovery of Québec and Nouveau-Québec Since 12,000 BP - Andrews, J.; Tyler, K. (Géographie physique et Quaternaire, 1977)
Radiocarbon dated relative sea levels, the tilts of proglacial lake shorelines and raised marine shorelines, the directions of the tilt of these features, and postglacial delevelling are used to construct six isobase maps showing relative sea level movements over the last 12,000, 10,000, 8000, 4000, and 2000 years, No map has more than 30 control points and usually there are only 12 "good" points controlling the isobase patterns. Each map shows the relationship of the isobases to the current ice sheet extent. Along the southern margin of the Laurentide Ice Sheet, the maximum postglacial emergence has been quite uniform with the 240 to 200 m isobase always close to the ice margin. Along the northeastern margin of the ice sheet, the postglacial emergence at the retreating ice edge was closer to 100 m. Equidistant diagrams are drawn along planes southeast from southern Hudson Bay and eastward from Southampton Island. If these diagrams are compared on a Shoreline Relation Diagram, the two profiles appear similar and compare moderately well with a theoretical SR Diagram published in 1969. The isobases show a major uplift center located around the area of James Bay and southern Hudson Bay where a maximum emergence of nearly 300 m occured in the last 7500 years. High marine limits southwest of Ungava Bay need to be dated because if they date close to 8000 BP as we suggest, then more emergence is suggested for the region southwest of Ungava Bay than we currently allow for.